VD_FINDINFO AI 190/13 - 177/2014 vom 9. Juli 2014 - VD Tribunal cantonal (2014)
ÉVALUATION DE L'INVALIDITÉ, AFFECTION PSYCHIQUE, SOMATISATION, DÉPRESSION, COMORBIDITÉ, EXPERTISE | 4 LAI, 6 LPGA, 7 LPGA, 8 LPGA